GazeRayHand: Combining Gaze Ray and Hand Interaction for Distant Object Manipulation - Sei Kang; Jaejoon Jeong; Soo-Hyung Kim; Hyung-Jeong Yang; Gun A. Lee; Seungwon Kim (Applied Sciences, 2025)
In this paper, we introduce novel techniques for distant object manipulation, named GazeRayHand and GazeRayHand2. The two techniques translate and rotate objects by using the gaze ray as a reference line and the hand position relative to the gaze ray. The GazeRayHand2 additionally supports gaze control for quick and long-distance object translation. We evaluate these techniques by comparing them with two other recent techniques: Gaze&Pinch and modified Gaze Beam Guided. In a user study, the results showed that GazeRayHand and GazeRayHand2 not only performed similarly to Gaze&Pinch, known for high performance, but also showed notable benefits. Both GazeRayHand and GazeRayHand2 significantly reduced unnecessary translation compared to other techniques and were rated highly by users for intuitiveness and ease of use. In contrast, Gaze&Pinch had an issue of requiring two hand interactions for rotation, causing inconvenience. The modified Gaze Beam Guided was the worst among the four techniques by compulsorily requiring unnecessary interaction.